Comparing self-assessment and instructor ratings: a study on communication and interviewing skills in psychology student training - Mats Najström; Martin Oscarsson; Ingrid Ljunggren; Jonas Ramnerö (BMC Medical Education)
Abstract Background A multitude of studies have investigated, assessed, and debated the merits of self-assessment within medical education and related fields, yielding inconclusive results. This raises questions about the reliability of self-assessment as a tool for evaluating competency development. The objective of the current study was to investigate the self-assessment accuracy of psychology students regarding their performance in training for interviewing and communication skills. A novel assessment instrument was employed for this purpose. The main research questions were: (1) How accurate are students’ self-assessments of their performance in comparison to instructors’ ratings? (2) How well do these self-assessments align with perceived changes in skill development at both group and individual levels? Methods The study was conducted in three phases to achieve the research objective. In Phase 1, 206 psychology students from the first three semesters of a 5-year master’s program at Stockholm University conducted 15-minute video-recorded interviews, which were rated by instructors using an 11-item assessment instrument. Data were analyzed using Exploratory Factor Analysis (EFA). Phase 2 included 173 second semester students conducting 15-minute video interviews. These were reviewed in small groups, with both students and instructors rating the interviews using the same instrument. The process was repeated after one week. Two Confirmatory Factor Analyses (CFAs) were conducted on instructors’ and students’ ratings to validate the three-factor model identified in Phase 1. In Phase 3, correlation analyses and paired-samples t-tests were conducted at both group and individual levels to address the research questions. Results The findings indicated high self-assessment accuracy, reflecting strong self-assessment abilities among the students. Comparisons between instructor ratings and students’ self-assessments of skill progression demonstrated good overall alignment. The validated assessment scale developed in Phases 1 and 2 shows potential for application in various educational contexts. Conclusions This study demonstrates that students are capable of evaluating their own interviewing and communication skills and can take an active role in their skill development when provided with suitable tools and adequate training. The findings support the viability of self-assessment as an educational tool and suggest its integration into psychology training programs, emphasizing clear criteria and reflective practices.